Oke-Ibadan Festival and the Ethnography of Aboke people of Ibadan - Oludele Mayowa Solaja; Adesina Abass Olayiwola (Yoruba Studies Review)
This study examines Oke-Ibadan festival and the ethnography of Aboke people of Ibadan. The objectives of the study are to document the cultural identity, fashion, family life-style, crafts, and hobbies of Aboke people; and, also, ascertain the significance of Oke-Ibadan festival to Aboke’s at home and abroad. Two sociological perspectives which include structural-functionalism and symbolic interactionism were used to provide a theoretical context for the study. The study adopts exploratory survey design which includes purposive and convenience sampling techniques. Thirty-five (35) participants were selected for the study. The instruments used in eliciting information from the participants were in-depth interview (IDI) guide and focus group discussion (FGD) guide, while the responses were gathered with the aid of electronic gadget such as the audio recorder. The data were analyzed using descriptive statistics, content analysis, and ethnography summary. The finding revealed that Aboke people have a unique cultural identity among other ethnic groups in Yorubaland. Their cultural identity as attested to by the participants include; hosting of Oke-Ibadan festival, retaining tribal mark, production of traditional/black soap for the cure of measles, narrating folk stories to the young generation in order to encourage high fertility rate, unique dress code, and acceptable physical appearance.